Optimal control analysis for the transmission of Nipah infection with imperfect vaccination - Mengqi Xie; Muhammad Younas Khan; Saif Ullah; Muhammad Farooq; Muhammad Bilal Riaz; Basem Al Alwan (PLoS ONE, 2025)
This paper presents an innovative mathematical model for assessing the dynamics and optimal control of Nipah virus (NiV) with imperfect vaccination. The model formulation considers transmissions through contaminated food and human-to-human contacts. It also incorporates the potential virus transmission through contact with a deceased body infected with NiV. Initially, the NiV model is assessed theoretically, identifying three distinct equilibrium states: the NiV-endemic equilibrium state, the NiV-free equilibrium state, and the equilibrium state involving infected flying foxes. Furthermore, the stability results of the model in the case of constant controls are thoroughly analyzed at the NiV-free equilibrium. Some of the parameters of the model are estimated based on the infected cases documented in Bangladesh from 2001 to 2017. We further perform sensitivity analysis to determine the most influential parameters and formulate effective time-dependent controls. Numerical simulations indicate the optimal course of action for eradicating the disease and provide a comparative analysis of controlling the infection under constant and time-varying interventions. The simulation confirms that the implementation of time-varying interventions is effective in minimizing disease incidence.